2013
DOI: 10.1063/1.4836878
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of detection-mechanism models of superconducting nanowire single-photon detector

Abstract: The microscopic mechanism of photon detection in superconducting nanowire single-photon detectors is still under debate. We present a simple but powerful theoretical model that allows us to identify essential differences between competing detection mechanisms. The model is based on quasi-particle multiplication and diffusion after the absorption of a photon. We then use the calculated spatial and temporal evolution of this quasi-particle cloud to determine detection criteria of three distinct detection mechani… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
75
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 50 publications
7
75
1
Order By: Relevance
“…For 220 nm-wide NbN SNSPDs made from nanobridges, and also with nanodetectors and meanders, the energy-current relation was found to be linear in the range of 0.75-8.26 eV using the quantum detector tomography (QDT). 24 A result consistent with this was found for TaN detectors 37 and for a series of NbN meanders of varying widths. 38 Nevertheless, a nonlinear behaviour for NbN meanders probed with a filtered black body light source was later observed in the 0.5-2.75 eV range 28 by using the two probability thresholds g ¼ 50% and 90% of the normalised PCR.…”
supporting
confidence: 74%
“…For 220 nm-wide NbN SNSPDs made from nanobridges, and also with nanodetectors and meanders, the energy-current relation was found to be linear in the range of 0.75-8.26 eV using the quantum detector tomography (QDT). 24 A result consistent with this was found for TaN detectors 37 and for a series of NbN meanders of varying widths. 38 Nevertheless, a nonlinear behaviour for NbN meanders probed with a filtered black body light source was later observed in the 0.5-2.75 eV range 28 by using the two probability thresholds g ¼ 50% and 90% of the normalised PCR.…”
supporting
confidence: 74%
“…The background of thermally excited QPs is neglected. This results in the coupled differential equations [105] ∂C e ( r, t) ∂t…”
Section: Diffusion-based Vortex-entry Modelmentioning
confidence: 99%
“…In [105] numerical results were compared with implementations of the normal-core hotspot model and the diffusion-based hotspot model within the same framework. The authors found clear indications that their new model and the underlying physics would lead to the entry of a vortex and thus the trigger of a normal domain before either of the other models predicts a detection event.…”
Section: Diffusion-based Vortex-entry Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…SSPDs have high efficiency, low jitter, low dark count rate and fast reset time [2], and are therefore a key technology for, among others, quantum key distribution Although progress has been made recently, the underlying physical mechanism responsible for photon detection on the nanoscale is still under active investigation. A combination of theory [6,7], experiments [8][9][10] and simulations [11,12] on NbN SSPDs indicates that the absorption of a photon destroys Cooper pairs in the superconductor and creates a localized cloud of quasiparticles that diverts current across the wire. This makes the wire susceptible to the entry of a superconducting vortex from the edge of the wire.…”
mentioning
confidence: 99%